Penerapan Model Pembelajaran Project Based Learning (PjBL) Berbantu Jobsheet untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Informatika - Anjjani Mardhika Adif; Lika Jafnihirda (Journal of Research and Investigation in Education, 2025)
This study aims to improve student learning outcomes using the Project Based Learning learning model assisted by jobsheets in the Informatics subject of class X hospitality 6 at SMK Negeri 9 Padang in the 2024/2025 Academic Year. This study uses a classroom action research method (classroom action research), using cycle I and Cycle II consisting of planning, implementation of actions, observation, and reflection. The research subjects were 36 students of class X hospitality 6. The results of the study showed that the Percentage of Completeness of the learning outcomes of class X hospitality 6 students in Cycle I was 78% and in Cycle II was 92% and the grades obtained by students in the Informatics subject through the use of the Project Based Learning learning model assisted by jobsheets increased from cycle I to cycle II by 14%. The conclusion of this study is that Informatics learning carried out using the Project Based Learning learning model assisted by Jobsheets can have a very significant influence on improving the learning outcomes of class X hospitality 6 students at SMK Negeri 9 Padang with the percentage of learning completeness in cycle I and cycle II.